Effect of Matra Basti and Katibasti in the Management of Lumbar Disc Disease - Sudesh Gupta, Dr (International Journal of Pharmaceutical & Biological Archive, 2013)
Effect of Matra Basti and Katibasti in the Management of Lumbar Disc Disease